Penilaian Kinerja Keuangan PT. Gudang Garam Tbk di BEI dengan Pendekatan Rasio Keuangan (Studi Kasus Periode 2019-2023) - Sriyatun; Aris Sugiarto (Politeknik Raflesia Press, 2025)
This study aims to comprehensively evaluate the financial performance of PT Gudang Garam Tbk (GGRM), one of Indonesia's leading cigarette manufacturers, during the turbulent period of 2019–2023. Using a descriptive-quantitative study design, this analysis applies a series of financial ratios, including liquidity, solvency, profitability, and efficiency as well as DuPont decomposition to dissect the determinants of Return on Equity (ROE). Secondary data were extracted from the company's annual reports and audited financial statements published through the Indonesia Stock Exchange (IDX). Key findings indicate significant pressure on GGRM’s profitability, reflected in sharp declines in Gross Profit Margin (GPM), Operating Profit Margin (OPM), and Net Profit Margin (NPM). This decline is primarily driven by faster-growing cost of goods sold than revenue growth, particularly due to the government’s aggressive increase in tobacco excise taxes (CHT). The DuPont analysis confirms that the decline in ROE is predominantly driven by the erosion of net profit margins, despite an increase in financial leverage. Meanwhile, liquidity ratios remain at healthy levels, but solvency ratios indicate an increase in risk as debt levels rise to fund expansion. The contribution of this research lies in presenting a narrative-analytical analysis that links quantitative data with regulatory and corporate strategy contexts, providing managerial implications and insights for investors in assessing the company's resilience and prospects amid industry challenges.